2021
DOI: 10.1126/scitranslmed.abi8452
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput cell- and virus-free assay shows reduced neutralization of SARS-CoV-2 variants by COVID-19 convalescent plasma

Abstract: The detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific antibodies in the serum of an individual indicates prior infection or vaccination. However, it provides limited insight into the protective nature of this immune response. Neutralizing antibodies recognizing the viral spike protein are more revealing, yet their measurement traditionally requires virus- and cell-based systems that are costly, time-consuming, inflexible, and potentially biohazardous. Here, we present a cell-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(136 citation statements)
references
References 41 publications
3
130
3
Order By: Relevance
“…However, some research use only kits for measuring RBD-ACE2r inhibiting antibodies are designed with plate bound RBD and soluble human ACE2r, without obvious explanation for this "reversed" orientation in regard to in vivo biophysics (e.g., cell surface bound ACE2r and soluble RBD). Recent work by Fenwick et al [25] in hospitalized COVID-19 patients using a soluble ACE2r-based binding format similar to the present study found strong correlations with PRNT, but did not study vaccinated individuals. The present data extend accumulating evidence that SARS-CoV-2 neutralizing capacity serum can be accomplished with competition assays based on soluble phase ACE2r attachment to immobilized spike or its RBD, and further demonstrate the utility of the approach in monitoring vaccine responses.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…However, some research use only kits for measuring RBD-ACE2r inhibiting antibodies are designed with plate bound RBD and soluble human ACE2r, without obvious explanation for this "reversed" orientation in regard to in vivo biophysics (e.g., cell surface bound ACE2r and soluble RBD). Recent work by Fenwick et al [25] in hospitalized COVID-19 patients using a soluble ACE2r-based binding format similar to the present study found strong correlations with PRNT, but did not study vaccinated individuals. The present data extend accumulating evidence that SARS-CoV-2 neutralizing capacity serum can be accomplished with competition assays based on soluble phase ACE2r attachment to immobilized spike or its RBD, and further demonstrate the utility of the approach in monitoring vaccine responses.…”
Section: Discussioncontrasting
confidence: 58%
“…In summary, we developed surrogate neutralization assay that significantly (p < 0.0001) correlates (rs=0.83) with IC50 measurements using live viral PRNT. The assay is similar in principle to methodology recently reported by Fenwick et al [25], but can be run with standard microtiter plate technology (vs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work is motivated by the urgent need for a rapid and easy-to-use assay that supplements conventional antibody neutralization tests that are labor-intensive, costly, require highly trained personnel, and are thus inaccessible in many regions around the world. While other assays have been developed that measure the ability of nAbs to block ACE2-RBD binding ( 33 , 34 , 37 ), to the best of our knowledge, CoVariant-SCAN is the first test that can detect nAbs against several SARS-CoV-2 variants simultaneously within 1 hour. Furthermore, because the CoVariant-SCAN is built upon a “nonfouling” polymer coating that eliminates nearly all nonspecific binding, the assay can be conducted directly from undiluted plasma ( 38 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, ACE2-GFP immobilized beads were used to bind the recombinant S1-RBD in a solution that is similar to the ELISA-based surrogate neutralizing antibody testing approach commercially available consisting of non-fluorescent h ACE2 and HRP based colorimetric detection (Fenwick et al, 2021). However, we have evaluated the best-known GFP immobilization approach, GFP nanobody, the single-chain VHH antibody domain of specific binding activity against GFP and its fusion proteins (Muyldermans et al, 2009) for direct visualization.…”
Section: Gfp/ofp Nanobody Based Immobilization Approach and Fluorescent Bead Assaymentioning
confidence: 99%